Analysis of the Relationship between Psychiatric and Addiction-Related Disorders in Patients of an Outpatient Addiction Treatment Clinic for Children and Adolescents - Jandac, Tomas; Stastna, Lenka (Children, 2024)
INTRODUCTION: Dual diagnosis is used in addiction medicine to refer to the co-occurrence of an addiction-related disorder and another psychiatric disorder in the same individual. Adolescence is a key period for the development of both mental disorders and addictions. OBJECTIVE: The aim of this study is to describe the relationships between psychiatric and addiction-related disorders in patients of the Outpatient Addiction Treatment Clinic for Children and Adolescents at the 1st Faculty of Medicine, Charles University in Prague in 2015-2022. METHODS: Data were retrospectively analyzed from the hospital's medical system, which collects basic diagnostic data on patients. Descriptive statistics and cluster analysis were performed to identify relationships between psychiatric and addiction-related disorders. RESULTS: Of the 450 patients, 153 patients (34%) met the criteria for dual diagnosis. The most common addiction-related disorders were mental and behavioural disorders due to the use of cannabinoids (35%) and internet gaming disorder (35%). The most common psychiatric diagnoses were behavioural and emotional disorders with usual onset in childhood and adolescence (64%), with a lower prevalence in girls than in boys. CONCLUSIONS: These findings may be important for the diagnosis and treatment of risky behaviours and addictions in children and adolescents.